Perlindungan Hukum dan Hak Asasi Manusia Bagi Prajurit TNI dalam Operasi Militer Selain Perang - Berlian Marpaung; Suparno Suparno (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Protection of human rights for TNI soldiers in carrying out their duties in general and OMSP is very important to guarantee the welfare and protect soldiers in serving the country. Protection of human rights for TNI soldiers in carrying out their duties and during OMSP is an important thing to guarantee. One example of human rights violations against TNI soldiers is the number of soldiers who died during law enforcement operations in Papua, where TNI soldiers became victims and lost their right to live due to the prolonged conflict situation in Papua which was caused by development failure, marginalization and discrimination of indigenous Papuans. state violence and accusations of human rights violations, as well as the history and political status of the Papua region. The conclusion of this research is that human rights protection for TNI soldiers in carrying out their duties in general and when carrying out OMSP is provided in the form of a legal framework for movement which is prepared by authorized officials and provided before soldiers carry out OMSP duties to protect soldiers from human rights violations that are prone to occur while soldiers are on duty in the operational field.